Thaumarchaeal ecotype distributions across the equatorial Pacific Ocean and their potential roles in nitrification and sinking flux attenuation - Alyson E. Santoro; Mak A. Saito; Tyler J. Goepfert; Carl H. Lamborg; Chris L. Dupont; Giacomo R. DiTullio (Limnology and Oceanography, 2017)
Thaumarchaea are among the most abundant microbial groups in the ocean, but controls on their abundance and the distribution and metabolic potential of different subpopulations are poorly constrained. Here, two ecotypes of ammonia‐oxidizing thaumarchaea were quantified using ammonia monooxygenase ( amoA ) genes across the equatorial Pacific Ocean. The shallow, or water column “A” (WCA), ecotype was the most abundant ecotype at the depths of maximum nitrification rates, and its abundance correlated with other biogeochemical indicators of remineralization such as NO 3 : Si and total Hg. Metagenomes contained thaumarchaeal genes encoding for the catalytic subunit of the urease enzyme ( ureC ) at all depths, suggesting that members of both WCA and the deep, water column “B” (WCB) ecotypes may contain ureC . Coupled urea hydrolysis‐ammonia oxidation rates were similar to ammonia oxidation rates alone, suggesting that urea could be an important source of ammonia for mesopelagic ammonia oxidizers. Potential inducement of metal limitation of both ammonia oxidation and urea hydrolysis was demonstrated via additions of a strong metal chelator. The water column inventory of WCA was correlated with the depth‐integrated abundance of WCB, with both likely controlled by the flux of sinking particulate organic matter, providing strong evidence of vertical connectivity between the ecotypes. Further, depth‐integrated amoA gene abundance and nitrification rates were correlated with particulate organic nitrogen flux measured by contemporaneously deployed sediment traps. Together, the results refine our understanding of the controls on thaumarchaeal distributions in the ocean, and provide new insights on the relationship between material flux and microbial communities in the mesopelagic.